2016
DOI: 10.1002/adfm.201505256
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Thermal Phenomena in the Vicinity of Magnetic Nanoparticles in Alternating Magnetic Fields

Abstract: Magnetic nanoparticles can be made to dissipate heat to their immediate surroundings in response to an applied alternating magnetic field. This property, combined with the biocompatibility of iron oxide nanoparticles and the ability of magnetic fields to penetrate deep in the body, makes magnetic nanoparticles attractive in a range of biomedical applications where thermal energy is used either directly to achieve a therapeutic effect or indirectly to actuate the release of a therapeutic agent. Although the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 74 publications
2
65
0
Order By: Relevance
“…Despite the arguments against nanoscale thermal phenomena, experimental evidence highlights the benefits of heating effects in the vicinity of magnetic nanoparticles, which could actually enhance the thermal potentiation of chemotherapeutic agents. 3,49 Second, the mechanism of action of PES to induce cancer cell death can be further enhanced by one of the mechanisms triggered by MFH. PES inhibits the function of stress-inducible heat-shock proteins (HSP70 family), which support lysosome membrane integrity, though lysosomal membrane permeabilization has also been identified as one of the death pathways after exposure to AMF.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the arguments against nanoscale thermal phenomena, experimental evidence highlights the benefits of heating effects in the vicinity of magnetic nanoparticles, which could actually enhance the thermal potentiation of chemotherapeutic agents. 3,49 Second, the mechanism of action of PES to induce cancer cell death can be further enhanced by one of the mechanisms triggered by MFH. PES inhibits the function of stress-inducible heat-shock proteins (HSP70 family), which support lysosome membrane integrity, though lysosomal membrane permeabilization has also been identified as one of the death pathways after exposure to AMF.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic moments of MNPs offer a plausible energetic handle for actuation by AMFs of this amplitude, 10 and experimental evidence has surprisingly indicated that nanoscale heating of MNPs is orders of magnitude greater than what macroscopic heat transport equations predict. 11 Scrutiny of indiscriminate use of linear response theory, the predominant physical model used to describe MNP hysteresis in AMFs, has led to the development and experimental evaluation of more general models. [12][13][14][15][16][17] These systems will likely continue to pose worthwhile fundamental questions and offer opportunities for applications in medicine and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In hyperthermia, the magnetic properties of nanoparticles are transferred into heat and dissipated to the surrounding environment, whereas the released energy of particles is corresponding to a hysteresis loop. It is described that the dissipated heat of a magnetite nanoparticle is dependent upon its size and composition, but furthermore, upon the frequency the temperature of the applied field [ 42 ]. The polyR-Fe 3 O 4 achieve 2.5 times higher specific heating power (SHP) than a previously approved contrast agent ferumoxides (Endorem/Feridex ® ) (208 W g −1 vs. 83 W g −1 ) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%